Estilo de vida y estrés postraumático en mujeres desplazadas víctimas de abuso sexual en Santa Marta, Colombia (2023)
Introduction: The phenomenon of forced displacement in Colombia is a consequence of the violence perpetrated by various illegal armed actors affecting the stability of a particular sector of the population and the country. Objective: To identify the relationship between lifestyle and post-traumatic stress disorder in a group of displaced women who were victims of sexual abuse. Methods: Descriptive correlational research with cross-sectional design and intentional sampling. Population constituted by 100 displaced women victims of sexual abuse, in which it was taken an intentional sample of 20 women, between 20 and 55 years old who accepted to participate, and other 20 displaced women. It was applied the Fantastic questionnaire of lifestyle and the Post-traumatic stress disorder´s symptoms severity scale. For the statistical analysis, descriptive analyzes were made, it was applied the student's T test for difference of means, and Spearman's Rho to determine the intensity of the correlation between the two variables studied. Results: After a 1 to 5 years´ time of re-experiencing, 80% of displaced women victims of sexual abuse were in severe chronic level of post-traumatic stress disorder, unlike the 35 % of non-victim displaced women. The 40 % of the displaced women victims of sexual abuse presented an inadequate lifestyle, unlike the 15 % of the non-victims displaced women. Conclusions: The negative impact of post-traumatic stress disorder lasts more in women who have suffered a double victimization than in those who only suffered forced displacement. This difficult situation undoubtedly affects the health and lifestyle of this population, although in the present study there was no evidence of correlation between lifestyle and post-traumatic stress disorder. © 2020, Editorial Ciencias Medicas. All rights reserved.